Characterization of gamma-glutamyl transpeptidase from Helicobacter pylori: An in-silico study - Nadia Hussain,; Saboor Muarij Bunny,; Amal H. I. Al Haddad,; Asia Khatoon,; Alisha Noor,; Fatima Muccee, (Dialogue Social Science Review (DSSR), 2025)
Gamma-glutamyl transpeptidase (ggT) of H. pylori origin has been documented as frequently associated with human gastroduodenal infections. Inhibition of this virulence factor may help in reducing the incidence of gastric cancer. Current study was performed to explore the characteristics of ggT enzyme. Sequence of protein was retrieved from Uniprot database and analyzed through SOPMA tool, SWISSMODEL server, STRING and QUICKGO tools. The alpha helix, extended strand and random coil contents were demonstrated as 33.33, 16.75 and 49.91, respectively. The tertiary (3D) structural analysis revealed complex folding and monomeric nature of protein. The glnA, P5CDH, pepA, gdhA, ansA, dapE, VacA, gatA, cysM and tuf were found as proteins that interact with ggT. The GO analysis showed glutathione hydrolase, biosynthetic and catabolic activities alongwith acyltransferase and transferase functions of ggT. This enzyme plays role in colonization of stomach cells by H. pylori. Exploring its characteristics might help in designing therapeutic approaches for inhibition of ggT, thus preventing bacterium from colonizing the gut. Keywords: gastric cancer, Helicobacter pylori, gamma-glutamyl transpeptidase, SWISSMODEL, inhibition